1992
DOI: 10.1046/j.1469-0705.1992.02010006.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic amniocentesis in twin pregnancies: results of a multicenter study of 529 cases

Abstract: To evaluate the risk of abortion after genetic amniocentesis in twin pregnancies, a retrospective study of 15 centers was performed. The spontaneous abortion rate up to 20 completed weeks of gestation was 2.3%; the abortion rate up to 28 completed weeks, as defined by WHO, was 3.7%. The abortion rate could not be correlated either with the number of needle insertions or with the type of marker dye used. There was also no correlation between the abortion rate and the gestational age at which amniocentesis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Coleman et al [24] reported a proportion of fetal losses of 5.0% before the 28th week of gestation. Multicenter studies including a high number of cases put fetal loss before the 28th week of pregnancy at 3.8% [8]. In the sample of pregnant women examined by us, the spontaneous loss rate in multiple pregnancies was found to be 5.89% between the 18th and the 28th gestational week.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Coleman et al [24] reported a proportion of fetal losses of 5.0% before the 28th week of gestation. Multicenter studies including a high number of cases put fetal loss before the 28th week of pregnancy at 3.8% [8]. In the sample of pregnant women examined by us, the spontaneous loss rate in multiple pregnancies was found to be 5.89% between the 18th and the 28th gestational week.…”
Section: Discussionmentioning
confidence: 76%
“…In multiple pregnancies, the incidence of chromosomal disorders grows parallel to the frequency of [2,8,9,16]. It is also well known that in multiple pregnancies the risk of fetal anatomical disorders and maternal age-specific chromosomal disorders is higher [4,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use fetal loss rate data from the multicentre study of Pruggmeyer et al (1992), because this study provides the most recent and complete results after prenatal diagnosis in twin pregnancies. In the present study, it is assumed that the fetal loss rate and the risk of prenatal diagnosis are the same for all maternal ages.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 1 shows the pregnancy loss rates before 20 and 28 weeks' gestation in various studies [12][13][14][15][16][17][18][19][20]. Pregnancy loss rates in these studies ranged from 0 to 6% up to 20 weeks and from 0 to 8% up to 28 weeks.…”
Section: Loss Rates After Amniocentesis In Multiple Gestationsmentioning
confidence: 98%